"Stuck in the ICU": Caring for Children With Chronic Critical Illness*. Issue 11 (November 2017) - Henderson, Carrie M.; Williams, Erin P.; Shapiro, Miriam C.; Hahn, Emily; Wright-Sexton, Laura; Hutton, Nancy; Boss, Renee D.
Abstract : Objective: Neonatal ICUs and PICUs increasingly admit patients with chronic critical illness: children whose medical complexity leads to recurrent and prolonged ICU hospitalizations. We interviewed participants who routinely care for children with chronic critical illness to describe their experiences with ICU care for pediatric chronic critical illness. Design: Semi-structured interviews. Interviews were transcribed and analyzed for themes. Setting: Stakeholders came from five regions (Seattle, WA; Houston, TX; Jackson, MS; Baltimore, MD; and Philadelphia, PA). Subjects: Fifty-one stakeholders including: 1) interdisciplinary providers (inpatient, outpatient, home care, foster care) with extensive chronic critical illness experience; or 2) parents of children with chronic critical illness. Interventions: Telephone or in-person interviews. Measurements and Main Results: Stakeholders identified several key issues and several themes emerged after qualitative analysis. Issues around chronic critical illness patient factors noted that patients are often relocated to the ICU because of their medical needs. During extended ICU stays, these children require longitudinal relationships and developmental stimulation that outstrip ICU capabilities. Family factors can affect care as prolonged ICU experience leads some to disengage from decision-making. Clinician factors noted that parents of children with chronic critical illness are often experts about their child's disease, shifting the typical ICU clinician-parent relationship. Comprehensive care for children with chronic critical illness can become secondary to needs of acutely ill patients. Lastly, with regard to system factors, stakeholders agreed that achieving consistent ICU care goals is difficult for chronic critical illness patients. Conclusions: ICU care is poorly adapted to pediatric chronic critical illness. Patient, family, clinician, and system factors highlight opportunities for targeted interventions toward improvement in care.